EFEKTIFITAS INTERVENSI MOTIVASI EKSTERNAL TERHADAP PENGENDALIAN BERAT BADAN - Sarahdeaz Siti Fazzaura Putri (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2022)
Background: Lifestyle behavior modification is a strategy in the management of obesity. The use of financial incentives is part of the external motivation in weight control programme. This intervention pattern is used to encourage healthy lifestyle behavior by providing direct rewards that depend on individual involvement in healthy lifestyle behaviors. Objective: To examine the overall effect of a study using a 6-month financial incentive intervention on weight loss control. Methods: Data were analyzed from studies reporting the use of financial incentive interventions with the resulting weight changes in the PubMed database. Then a meta-analysis was performed to assess the overall effect. Results: The meta-analysis involved a total of 13 studies. The overall effect shows that the financial incentive intervention has a significant effect on weight loss. There was a significant difference in weight loss in the group that was given financial incentive intervention for 6 months compared to the control group (SMD: -0.49; 95% CI). Statistical heterogeneity was found (I2 = 95.20%, P = 0.00). The random effects model was used in the analysis. Conclusion: There was a significant effect between the financial incentive intervention for 6 months and weight loss although heterogeneity was found between studies. Keywords: Financial Incentives, Meta-analysis, Obesity